Method for measuring tanning strength of leather cultural relics

The lateral stacking distance of leather cultural relics samples was measured by synchronous radiation light source wide-angle X-ray one-dimensional diffraction technology, and the tanning strength was calculated, which solved the problem of complex detection methods and damage cultural relics in the prior art, and achieved lossless, fast and efficient tanning strength determination.

CN119643608AActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411852144.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-18
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing leather cultural relics tanning strength detection methods are complex in operation and cause irreversible damage to cultural relics, so they cannot effectively quantify the tanning strength of leather cultural relics.

Method used

The tanning intensity is calculated by measuring the lateral stacking distance of leather cultural relics samples by synchronous radiation light source wide-angle X-ray one-dimensional diffraction technology. This method is used to measure when the moisture content is 5%-10%, ensuring the accuracy of the detection results.

Benefits of technology

A lossless, fast and efficient measurement of tanning strength of leather cultural relics is achieved, avoiding damage to cultural relics, and significantly improving the measurement efficiency and accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643608A_ABST
    Figure CN119643608A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of leather cultural relic protection, and discloses an efficient and lossless leather cultural relic tanning strength determination method. According to the method, a synchronous radiation light source is adopted to obtain a wide-angle X-ray one-dimensional diffraction pattern of a leather cultural relic sample (the moisture content is 5%-10%), the transverse stacking distance between collagen molecules is calculated through the pattern, the tanning strength is calculated according to the transverse stacking distance, and rapid, lossless and accurate quantification of the tanning strength of the leather cultural relic is achieved. The method effectively solves the problems of scarcity of samples, irregular shapes and the like, and provides reliable scientific data support for evaluating the stability of leather cultural relics and developing preventive protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of leather cultural relic protection, and particularly relates to a method for measuring the tanning strength of leather cultural relics. Background Art

[0002] As an important carrier of human civilization, leather artifacts have witnessed the changes of history and the inheritance of culture. They are of great significance for studying human society, promoting cultural exchanges, and exploring ancient craftsmanship. Tanning is a key process for converting raw hides into leather. The accurate determination of its strength is crucial for evaluating the durability, stability, and corrosion resistance of leather artifacts, thereby providing reliable data support for the formulation of scientific restoration plans. Therefore, it has important value in the field of cultural relic protection and restoration. However, since leather artifacts are fragile and easily affected by environmental factors, the existing detection methods suitable for modern leather tanning strength (such as leather shrinkage temperature or thermal denaturation temperature) are not only complicated to operate, but also cause irreversible damage to the artifacts. Therefore, there is an urgent need to develop new methods suitable for quantifying the tanning strength of leather artifacts to fill the technical gap in this field. Summary of the invention

[0003] In order to solve the problems existing in the background technology, the present invention aims to provide an efficient, practical and non-destructive method for determining the tanning strength of leather artifacts.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is: The determination method of the tanning strength of leather artifacts includes the following steps: The test obtained the synchrotron radiation light source wide-angle X-ray one-dimensional diffraction spectrum of the leather cultural relic sample; the moisture content of the sample was 5%-10%; Calculating the lateral stacking distance between sample collagen molecules according to the wide-angle X-ray one-dimensional diffraction pattern of the synchrotron radiation light source; The tanning strength of the sample is calculated according to the lateral stacking distance, and the calculation formula is: S=(1.30-D) / 1.30×100%; wherein S is the tanning strength, D is the lateral stacking distance, and 1.30 is the standard lateral stacking distance between untanned skin collagen molecules, in nm.

[0005] Preferably, the distance between the sample and the detector during the synchrotron radiation source wide-angle X-ray scattering test is 30-50 cm.

[0006] Preferably, the test time of the synchrotron radiation source wide-angle X-ray scattering is 0.1-2 s.

[0007] Preferably, the energy range of wide-angle X-ray scattering of the synchrotron radiation source is 8-15 keV.

[0008] Preferably, the leather cultural relic samples include any one of aluminum-tanned leather cultural relics, iron-tanned leather cultural relics, smoke-tanned leather cultural relics, oil-tanned leather cultural relics, nitrated leather cultural relics, nitre-tanned leather cultural relics, parchment cultural relics, and shadow puppet cultural relics.

[0009] Preferably, the leather artifact sample comprises any one of leather pieces, leather residues and leather particles.

[0010] Preferably, the calculation formula of the lateral stacking distance is: D = 2π / q; wherein q is the horizontal coordinate value of the characteristic peak representing the distance between collagen molecules in the one-dimensional spectrum, and the unit is nm. -1 .

[0011] The present invention uses synchrotron radiation light source wide-angle X-ray scattering technology to measure the tanning intensity of leather artifacts, which has the following advantages over the prior art: (1) Non-destructive protection technology: The use of non-destructive detection methods completely avoids potential risks to the structure of cultural relics, ensures the original state and integrity of cultural relics, and meets the non-destructive standards for cultural relic protection.

[0012] (2) Efficient and rapid identification technology: This technology can quickly provide accurate measurement results within 0.1 to 2 seconds, significantly shortening the test cycle, greatly improving the measurement efficiency, effectively reducing the cost of manpower and time, and providing strong support for cultural relics protection work.

[0013] (3) Widely applicable identification technology: This technology is highly adaptable and is not limited by the shape, state or preservation conditions of the cultural relics. It does not require complicated pre-processing steps and can be directly applied to the identification of various leather cultural relics, providing a more convenient and efficient testing method for cultural relic protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the measurement of the tanning reaction intensity of tanning agents and collagen using wide-angle X-rays from a synchrotron radiation source. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention. In the embodiment, those who do not indicate specific conditions are carried out according to the conditions recommended by normal conditions or manufacturers. Those who do not indicate manufacturers for reagents or instruments used are conventional products that can be obtained by commercial purchase.

[0016] Shrinkage temperature or thermal denaturation temperature test is a method widely used in modern leather tanning strength detection. However, these two test methods are not only cumbersome to operate, but also cause irreversible damage to cultural relics. Through a large number of synchrotron radiation light source wide-angle X-ray scattering tests, the applicant found that under specific moisture content (5%-10%) conditions, the tanning strength of leather cultural relics is positively correlated with the degree of reduction in the lateral stacking distance between its collagen molecules. Specifically, the tanning process involves a chemical cross-linking reaction between tanning agent molecules and collagen molecules. The higher the tanning intensity, the stronger the cross-linking reaction, and the shorter the lateral stacking distance between collagen molecules. Based on this finding, the applicant defines the tanning strength of leather cultural relic samples as the degree of reduction in the lateral stacking distance between collagen molecules. The greater the reduction, the stronger the tanning strength. This method is not only easy to operate, but also belongs to a non-destructive testing technology, which effectively overcomes the shortcomings of existing leather tanning strength testing technology.

[0017] refer to Figure 1 The present invention provides a method for determining the tanning strength of leather artifacts, and the determination steps are as follows: The test obtained the synchrotron radiation light source wide-angle X-ray one-dimensional diffraction spectrum of the leather cultural relic sample; the moisture content of the sample was 5%-10%; Calculating the lateral stacking distance between sample collagen molecules according to the wide-angle X-ray one-dimensional diffraction pattern of the synchrotron radiation light source; The tanning strength of the sample is calculated according to the lateral stacking distance, and the calculation formula is: S=(1.30-D) / 1.30×100%; wherein S is the tanning strength, D is the lateral stacking distance, and 1.30 is the standard lateral stacking distance between untanned skin collagen molecules, in nm.

[0018] Since high moisture content will increase background scattering, reduce the overall electron density of the leather cultural relic sample, affect the reliability of the data, and cannot accurately quantify the tanning intensity of the leather cultural relic; at the same time, the presence of bound water in the leather makes its moisture content unable to be lower than 5%. Therefore, in the embodiment of the present invention, the moisture content of the leather cultural relic sample must be between 5% and 10% to ensure the accuracy of the detection result.

[0019] Based on the above theory, the present invention is applicable to the determination of the tanning strength of all leather artifacts with a moisture content of 5%-10%. For example, the leather artifacts discovered so far include aluminum tanned leather artifacts, iron tanned leather artifacts, smoke tanned leather artifacts, oil tanned leather artifacts, nitrate tanned leather artifacts, nitrated leather artifacts, parchment artifacts, and shadow puppet artifacts; during the determination, the leather artifact sample can be in the form of leather pieces, leather residues, leather particles, and other shapes that are convenient for determination.

[0020] It should be noted that the lateral stacking distance refers to the lateral stacking distance between collagen molecules. The prior art has realized the calculation of the lateral stacking distance between molecules through the wide-angle X-ray one-dimensional diffraction spectrum of the synchrotron radiation light source. The present invention also uses the calculation formula of the prior art to calculate. Specifically: D = 2 π / q; where q is the horizontal coordinate value of the characteristic peak representing the distance between collagen molecules in the one-dimensional spectrum, and the unit is nm -1 .

[0021] In the embodiment of the present invention, the distance between the sample and the detector can be set by a person skilled in the art according to the X-ray energy of the synchrotron radiation source wide-angle X-ray scattering experimental station and the effective area of ​​the detector. Under this condition, the leather should obtain a clear characteristic peak of the lateral stacking distance between collagen molecules through the detector. For example, the distance between the sample and the detector can be set to 30-50 cm.

[0022] In the embodiment of the present invention, the setting of the test time and X-ray energy of the sample can be selected by a person skilled in the art according to the actual thickness of the sample, as long as the characteristic peak of the lateral stacking distance between collagen molecules of the sample can be obtained by the detector. For example, the test time can be set to 0.1-2s and the X-ray energy can be set to 8-15 keV.

[0023] In order to make the technical solution of the present invention clearer, the method for determining the tanning strength of leather artifacts is described in detail below through multiple specific embodiments and comparative examples.

[0024] The synchrotron radiation wide-angle X-ray scattering experiment in the embodiment of the present invention is carried out at the Shanghai Light Source Synchrotron Radiation Wide-angle X-ray Scattering Experiment Station, and the equipment model used is the PILATUS 1M detector.

[0025] Due to the scarcity of leather artifact samples, ancient leather simulation samples were used in the comparative examples and embodiments. The preparation methods of different simulation samples are as follows: Ancient aluminum tanned leather simulation sample: In ancient Chinese chemistry, "alum" was often used to refer to metal sulfate. Alum is a common natural mineral with a long history and is widely used in leather making. The aluminum salt in alum can react with the carboxyl group of skin collagen to achieve chemical cross-linking. Therefore, aluminum sulfate was used as an aluminum tanning agent for the tanning process, and sulfonated rapeseed oil, sulfated castor oil and hot water were mixed and stirred into an emulsion in a mass ratio of 2:1:9, and evenly applied to the flesh side of the tanned leather. After standing, drying on a stretcher and softening, the ancient aluminum tanned leather simulation sample was obtained.

[0026] Ancient oil-tanned leather simulation sample: Oil tanning is one of the oldest tanning methods. Ancient humans first used natural oils, such as brains and fats of pigs, cattle and sheep, fish oil or vegetable oil as tanning materials, and relied on manual kneading operations to make leather. Therefore, fish oil with high unsaturation was used for the tanning process, and the treated leather samples were oxidized at 40°C and relative humidity of 90%~100% for 4 days, and then washed with alkali, hung to dry, and softened by hand, thrashed for 2 hours, and oscillated and softened 3 times to obtain the ancient oil-tanned leather simulation sample.

[0027] Ancient iron-tanned leather simulation sample: The tanning agent used in iron tanning may come from the mineral yellow vitriol. The main component of natural yellow vitriol is KFe3(SO4)2(OH)6, and some yellow vitriol is Fe3(SO4)2·9H2O formed by weathering and oxidation of natural green vitriol. The iron complex reacts with the carboxyl group of collagen to form chemical cross-links between the collagen in the skin. Therefore, when developing the iron tanning retro process, iron sulfate was selected as the iron tanning agent for tanning, and 10% sulfonated rapeseed oil and 5% sulfated castor oil based on the weight of the tanned leather were used for emulsion fatliquoring of the tanned leather. After hanging drying and softening, the ancient iron-tanned leather simulation sample was obtained.

[0028] Ancient smoked tanned leather simulation sample: In ancient times, in order to prolong the storage time of animal skins and avoid decay, the ancients discovered that smoke fumigation could prevent animal skins from deteriorating. The volatile aldehydes and phenols in the smoke can combine with the collagen of the skin to produce a tanning effect. This is the origin of the smoke tanning method (aldehyde tanning method). Since firewood is mainly composed of lignocellulose, its pyrolysis products furfural and guaiacol can simulate the volatile small molecules in the smoke. Therefore, furfural and guaiacol are used as smoke tanning agents for the tanning process, and sulfonated rapeseed oil, sulfated castor oil and hot water are mixed and stirred into an emulsion in a mass ratio of 2:1:9, and evenly applied to the flesh surface of the tanned leather. After standing, drying on a stretcher and softening, the ancient smoked tanned leather simulation sample is obtained.

[0029] Ancient nitrate tanned leather simulation sample: The use of Glauber's salt (Na2SO4·10H2O) in Chinese history can be traced back to the appearance of the word "nitrate" in seal scripts during the Warring States Period. Glauber's salt is an important chemical for leather making in ancient times. The nitrate tanning method using Glauber's salt and flour to make leather is one of my country's traditional leather making processes. Its tanning agent raw materials are convenient and easy to obtain, and the tanning method is simple. Therefore, Glauber's salt and starch are used as nitrate tanning agents for the tanning process, and sulfonated rapeseed oil, sulfated castor oil and hot water are mixed and stirred into an emulsion in a mass ratio of 2:1:9, and evenly applied to the flesh side of the tanned leather. After standing, drying on a stretching board and vibration softening, the ancient iron tanned leather simulation sample is obtained.

[0030] In the specific embodiments and comparative examples of the present invention, the method for determining the shrinkage temperature of the ancient leather simulation sample is: The shrinkage temperature of the ancient leather simulation samples was measured using a MSW-YD4 digital leather shrinkage temperature tester.

[0031] The present invention has designed 8 embodiments and 8 comparative examples. In these embodiments, the moisture content of the ancient leather simulation samples is strictly controlled between 5% and 10% by a drying method; while in the comparative examples, the moisture content of the ancient leather simulation samples is more than 10% by constant temperature and humidity regulation. As it is well known in the art that the tanning strength of leather is positively correlated with the shrinkage temperature of leather, the accuracy of the tanning strength measurement result can be reflected by the change relationship between the tanning strength and the shrinkage temperature measured in the embodiments and comparative examples.

[0032] Example 1 The test obtained the synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient nitrate tanning simulation sample (leather block) with a moisture content of 6%. The X-ray energy was 15 keV, the distance from the sample to the Pilatus 1MF detector was 50 cm, and the exposure time was 1 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient nitrate tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient nitrate tanning simulation sample.

[0033] According to the measurement, the lateral stacking distance between collagen molecules of the ancient nitrate tanning simulation sample with a moisture content of 5% in this embodiment is 1.25 nm, and the tanning strength is 3.85%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0034] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that the moisture content of the ancient nitrate tanning simulation sample (leather block) is 30%. According to the measurement, the lateral stacking distance between collagen molecules is 1.18 nm, and the tanning strength is 9.23%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0035] Example 2 The test obtained the synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient aluminum tanning simulation sample (leather block) with a moisture content of 8%. The X-ray energy was 15 keV, the distance from the sample to the Pilatus 1MF detector was 35 cm, and the exposure time was 0.1 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient aluminum tanning simulation sample.

[0036] It was determined that the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample with a moisture content of 8% in this embodiment was 1.22 nm, and the tanning strength was 6.15%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0037] Comparative Example 2 Compared with Example 2, the difference of Comparative Example 2 is that the moisture content of the ancient aluminum tanning simulation sample (leather block) is 50%. After measurement, the lateral stacking distance between collagen molecules is 1.19 nm, and the tanning strength is 8.46%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0038] Example 3 The test obtained the synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient aluminum tanning simulation sample (leather block) with a moisture content of 8%. The X-ray energy was 10 keV, the distance from the sample to the Pilatus 1MF detector was 30 cm, and the exposure time was 0.1s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient aluminum tanning simulation sample.

[0039] It was determined that the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample with a moisture content of 8% in this embodiment was 1.18 nm, and the tanning strength was 9.23%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0040] Comparative Example 3 Compared with Example 3, the difference of Comparative Example 3 is that the moisture content of the ancient aluminum tanning simulation sample (leather block) is 50%. After measurement, the lateral stacking distance between collagen molecules is 1.22 nm, and the tanning strength is 6.15%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0041] Example 4 The test obtained the synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient smoke tanning simulation sample (leather particles) with a moisture content of 5%. The X-ray energy was 15 keV, the distance from the sample to the Pilatus 1MF detector was 40 cm, and the exposure time was 1 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient smoke tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient smoke tanning simulation sample.

[0042] It was determined that the lateral stacking distance between collagen molecules in the ancient smoke tanning simulation sample with a moisture content of 5% in this embodiment was 1.15 nm, and the tanning strength was 11.54%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0043] Comparative Example 4 Compared with Example 4, the difference of Comparative Example 4 is that the moisture content of the ancient smoke tanning simulation sample (leather particles) is 30%. According to the measurement, the lateral stacking distance between collagen molecules is 1.20 nm, and the tanning strength is 7.69%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0044] Example 5 The synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient aluminum tanning simulation sample (leather block) with a moisture content of 8% was tested. The X-ray energy was 8 keV, the distance from the sample to the Pilatus 1MF detector was 35 cm, and the exposure time was 2 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient aluminum tanning simulation sample.

[0045] It was determined that the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample with a moisture content of 8% in this embodiment was 1.11 nm, and the tanning strength was 14.62%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0046] Comparative Example 5 Compared with Example 5, the difference of Comparative Example 5 is that the moisture content of the ancient aluminum tanning simulation sample (leather block) is 50%. After measurement, the lateral stacking distance between collagen molecules is 1.21 nm, and the tanning strength is 6.92%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0047] Example 6 The synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient oil tanning simulation sample (leather residue) with a moisture content of 5% was tested, the X-ray energy was 10 keV, the distance from the sample to the Pilatus 1MF detector was 50 cm, and the exposure time was 1 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient oil tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning intensity of the ancient oil tanning simulation sample.

[0048] It was determined that the lateral stacking distance between collagen molecules in the ancient oil tanning simulation sample with a moisture content of 5% in this embodiment was 1.10 nm, and the tanning strength was 15.39%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0049] Comparative Example 6 Compared with Example 6, the difference of Comparative Example 6 is that the moisture content of the ancient oil tanning simulation sample (leather residue) is 65%. According to the measurement, the lateral stacking distance between collagen molecules is 1.22 nm, and the tanning strength is 6.15%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0050] Example 7 The synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient aluminum tanning simulation sample (leather block) with a moisture content of 8% was tested, the X-ray energy was 10 keV, the distance from the sample to the Pilatus 1MF detector was 50 cm, and the exposure time was 2 s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient aluminum tanning simulation sample.

[0051] It was determined that the lateral stacking distance between collagen molecules in the ancient aluminum tanning simulation sample with a moisture content of 8% in this embodiment was 1.08 nm, and the tanning strength was 16.92%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0052] Comparative Example 7 Compared with Example 7, the difference of Comparative Example 7 is that the moisture content of the ancient aluminum tanning simulation sample (leather block) is 50%. After measurement, the lateral stacking distance between collagen molecules is 1.20 nm, and the tanning strength is 7.69%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0053] Example 8 The test obtained the synchrotron radiation source wide-angle X-ray one-dimensional diffraction pattern of the ancient iron tanning simulation sample (leather residue) with a moisture content of 10%, the X-ray energy was 10 keV, the distance from the sample to the Pilatus 1MF detector was 40 cm, and the exposure time was 0.1s. The formula D=2 π / q was used to calculate the lateral stacking distance between collagen molecules in the ancient iron tanning simulation sample. The formula S=(1.30-D) / 1.30×100% was used to calculate the tanning strength of the ancient iron tanning simulation sample.

[0054] It was determined that the lateral stacking distance between collagen molecules in the ancient iron tanning simulation sample with a moisture content of 10% in this embodiment was 1.05 nm, and the tanning strength was 19.23%. The shrinkage temperature of the sample was tested, and the results are shown in Table 1.

[0055] Comparative Example 8 Compared with Example 8, the difference of Comparative Example 8 is that the moisture content of the ancient iron tanning simulation sample (leather residue) is 40%. After measurement, the lateral stacking distance between collagen molecules is 1.18 nm, and the tanning strength is 9.23%. The shrinkage temperature of the sample is tested, and the results are shown in Table 1.

[0056] Table 1 .

[0057] According to the data analysis of Table 1, within the range of 5%-10% moisture content, the tanning strength and shrinkage temperature of different ancient leather simulation samples in Examples 1-8 show a positive correlation. In contrast, no correlation was observed between the tanning strength and shrinkage temperature of different ancient leather simulation samples in Comparative Examples 1-8. This is mainly because the moisture content in the comparative leather exceeds 10%, resulting in increased background scattering, reducing the overall electron density of the sample, and thus affecting the reliability of the data, making it impossible to accurately quantify the tanning strength of the sample. Therefore, the tanning strength determination method of the present invention is suitable for leather cultural relics with a moisture content of 5%-10%.

[0058] Through the analysis of the above embodiments and comparative examples, it can be clearly seen that the present method is efficient and practical in determining the tanning strength of leather cultural relics. In addition, its completely non-destructive testing method is not achievable by the prior art. The present invention uses synchrotron radiation light source X-ray scattering technology to determine the tanning strength of leather cultural relics. Compared with the prior art, it not only effectively solves the problems of sample scarcity and irregular morphology, but also significantly improves the accuracy and reliability of the test, which fully meets the requirements of non-destructive testing for cultural relic identification.

[0059] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for determining the tanning strength of leather artifacts, characterized in that: The measurement steps are: The test obtained the synchrotron radiation light source wide-angle X-ray one-dimensional diffraction spectrum of the leather cultural relic sample; the moisture content of the sample was 5%-10%; Calculate the lateral stacking distance between sample collagen molecules according to the wide-angle X-ray one-dimensional diffraction pattern of the synchrotron radiation light source; The tanning strength of the sample is calculated according to the lateral stacking distance, and the calculation formula is: S=(1.30-D) / 1.30×100%; wherein S is the tanning strength, D is the lateral stacking distance, and 1.30 is the standard lateral stacking distance between untanned skin collagen molecules, in nm.

2. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The distance between the sample and the detector during the wide-angle X-ray scattering test at the synchrotron radiation source is 30-50 cm.

3. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The test time of wide-angle X-ray scattering at synchrotron radiation source is 0.1-2 s.

4. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The energy range of wide-angle X-ray scattering at synchrotron radiation sources is 8-15 keV.

5. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The leather cultural relic samples include any one of aluminum tanned leather cultural relics, iron tanned leather cultural relics, smoke tanned leather cultural relics, oil tanned leather cultural relics, nitrated leather cultural relics, nitrate tanned leather cultural relics, parchment cultural relics, and shadow puppet cultural relics.

6. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The leather artifact sample may be in the form of any one of leather pieces, leather residues and leather particles.

7. The method for measuring the tanning strength of leather artifacts as claimed in claim 1, characterized in that: The calculation formula of the lateral stacking distance is: D = 2 π / q; where q is the horizontal coordinate value of the characteristic peak representing the distance between collagen molecules in the one-dimensional spectrum, and the unit is nm -1 .

Citation Information

Patent Citations

  • Large-area multi-characteristic ray surface analysis device

    CN113791098A

  • Quantitative determination method of hydrogen bond geometry based on phonon spectrum

    CN116256349A

  • Combined scanning type XRD / XRF comprehensive imaging device and method

    CN116879335A

  • Nondestructive rapid detection method for aging state of leather cultural relics

    CN118533934A

  • Preparation method of simulation samples of leather cultural relics with different aging degrees

    CN118777009A